From nomads of the steppes to citizens of Turkey: Turkish historiography of the Kazakh diaspora - Aktailak, B.B.; Ibrayemova, M.S.; Mutalova, D.S.; Baishov, B.B. (Karagandy University of the name of acad. E.A. Buketov, 2025)
The proposed article is devoted to studying the evolution of the image of Kazakhs in Turkish historiography. It will focus on analyzing how Turkish historians formed and transformed perceptions of Kazakhs during different historical periods. The study covers a wide time range, from the first contacts between Kazakhs and Turks to the present day. Special attention is paid to how political, social and cultural factors influenced the formation of stereotypes about Kazakhs in Turkish society. The article will consider such aspects as the evolution of the image of Kazakhs in the XX century; analyze changes in the perception of Kazakhs in connection with political events in Central Asia, and in the world as a whole. And also, much attention is paid to modern studies of the history of the Kazakh diaspora in Turkey, including an assessment of the level of scientific objectivity and relevance of contemporary works of Turkish historians devoted to this topic. The authors explore the main changes in the image of Kazakhs in Turkish historiography, what factors influenced it and what prospects are open for further research in this area. This study provides a deeper understanding of the peculiarities of relations between Kazakhs and Turks, as well as tracing how historical memory and stereotypes influence international relations.
Keywords: History of migrations; Intellectual history; Kazakhstan; Kazakhs in Turkey; Kazakh refugees; Identity; Historical memory; Hasan Oraltay; Turkish historiography; Kazakh diaspora